Congo Red Azo Dye Removal and Study of Its Kinetics by Aloe Vera Mediated Copper Oxide Nanoparticles - Madiha Batool; Muhammad Zahid Qureshi; Farwa Hashmi; Nida Mehboob; Abdul Salam Shah (Universitas Gadjah Mada, 2019)
Nanotechnology is generating interest of researchers toward cost-free and environment-friendly biosynthesis of nanoparticles. In this research, biosynthesis of stable copper nanoparticles has been done by using aloe vera leaves extract which has been prepared in de-ionized water. The aim of this study is the tracing of an object by green synthesis of copper oxide nanoparticles with the interaction of leaves extract and copper salt and its dye removal efficiency. The results have confirmed the efficient removal of Congo red (CR) dye using copper oxide nanoparticles. Furthermore, we have examined the effect of variables like concentration, time, pH, and adsorbent dosage. We have observed maximum 1.1 mg/g dye removal at 10 min time interval, pH 2, and 5 mg/g nanoparticles. The shape of the copper nanoparticles was spherical, and their range of grain was 80–120 nm. The EDX of synthesized nanoparticles showed copper 38% and 65% oxygen. UV spectrophotometer analysis confirms peak of the copper nanoparticles between 200–600 nm.